A Modified PFC Rectifier Based EV Charger Employing CC/CV Mode of Charging⁎This work is supported by Department of Heavy Industry, DHI under grant number, 3(04)/2018-NAB-II. Issue 2 (2020) - Tiwary, Anyuti; Singh, Mukesh
Abstract: Automobile industry has displayed an inclination towards Electric Vehicles (EVs). However, EVs charging throws inevitable challenges due to inclusion of non-linear charger circuitry. The conventionally utilized AC-DC rectification in charger poses ruinous effects to Grid and EV structure in the form of harmonics interference and obnoxious spikes in current. Thus, repercussions of elevated THD can be witnessed in poor efficiency and deterioration of EV charger. Furthermore, harmonics in input inductor current produce harmonics in rectifier's output voltage. This can lead to DC link voltage fluctuation and adversely affect DC/DC converter functioning. Henceforth, a Power Factor Correction (PFC) rectifier based charger has been proposed that eliminates unwanted harmonics from input current and reduces THD. Moreover, harmonics in rectifier's output voltage are reduced and constant DC link voltage is obtained. Sinusoidal input current is maintained through Critical Conduction Mode (CrCM) and hysteresis current control application. These are achieved using inner current and outer voltage control loop method. The former produces sinusoidal current wave in phase with input voltage to improve power factor. Whereas, latter helps in achieving constant DC link voltage. Hence, THD factor of 1.30% and power factor of 0.9998 are recorded. In addition, model inculcates CC/CV charging algorithm to control overcharging of battery. Here, battery charges at Constant Current (CC) initially. Once, maximum voltage is reached, charging occurs at Constant Voltage (CV). It is governed by two isolated PI controllers. The collaborated work of PFC and CC/CV helps in recording model's efficiency of 96.8%. Furthermore, a 2 kW charger prototype is analysed using real time simulation and validated through Hardware-in-loop (HIL) in OPAL-RT.